2014
DOI: 10.4236/sgre.2014.55010
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation of Apartment Buildings and Nursing Homes

Abstract: The paper presents the results of the investigations into the indoor climate and energy efficiency of ventilation devices in residential buildings and nursing homes. The indoor climate studies discussed in the article were conducted in a nursing home where room ventilation is based on Meltem Air Handling Units (AHU). Similar studies have been carried out in apartment buildings where CO2 levels in bedrooms were compared before and after renovating the ventilation with Meltem AHU and installing exhaust fans in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…In general, the authors justified the high concentrations found in their studies with the existence of insufficient ventilation rates and/or high occupancy density [9,18]. In fact, after a ventilation system renovation in Estonian nursing homes, Mikola et al [59] observed a remarkable reduction in indoor CO 2 levels, which complied with guidelines. Some authors reported the highest levels for bedrooms [9,38] and others for living rooms [39,58], drawing rooms [2], or dining rooms [2,58], with levels typically increasing during the afternoon period in areas where people stay for more time.…”
Section: Carbon Dioxidementioning
confidence: 64%
See 1 more Smart Citation
“…In general, the authors justified the high concentrations found in their studies with the existence of insufficient ventilation rates and/or high occupancy density [9,18]. In fact, after a ventilation system renovation in Estonian nursing homes, Mikola et al [59] observed a remarkable reduction in indoor CO 2 levels, which complied with guidelines. Some authors reported the highest levels for bedrooms [9,38] and others for living rooms [39,58], drawing rooms [2], or dining rooms [2,58], with levels typically increasing during the afternoon period in areas where people stay for more time.…”
Section: Carbon Dioxidementioning
confidence: 64%
“…For elderly centers, CO 2 is a popular parameter that has been included in most of the IAQ evaluations conducted. Results from these assessments show that indoor CO 2 concentrations above ASHRAE recommendations have been reported in the majority of the works [9,38,39,58,59], with a limited number of studies finding CO 2 levels below 1000 ppm [7,18]. In general, the authors justified the high concentrations found in their studies with the existence of insufficient ventilation rates and/or high occupancy density [9,18].…”
Section: Carbon Dioxidementioning
confidence: 86%
“…As shown by the study [17], in-wall ventilation inflow-exhaust units with heat recuperators can provide the necessary parameters of indoor air indoors and save heat energy when reconstructing ventilation systems in residential buildings. Together with the introduction of new standards for the quality of indoor air of premises in residential buildings, large-scale studies of the microclimate of existing buildings [17,18,19] are carried out in Estonia, the purpose of which is to establish of the need of using mechanical inflow and exhaust ventilation in such buildings. It has been established that individual energy efficiency measures do not significantly affect the use of energy.…”
Section: Main Materialsmentioning
confidence: 96%
“…Different variants of ventilation units with heat exchangers are investigated at Tallinn Technological University (TTU) and their efficiency in maintaining the parameters of microclimate of internal air both in laboratory (Fig. 5) and in real conditions [17]. As shown by the study [17], in-wall ventilation inflow-exhaust units with heat recuperators can provide the necessary parameters of indoor air indoors and save heat energy when reconstructing ventilation systems in residential buildings.…”
Section: Main Materialsmentioning
confidence: 99%
“…As the ventilation heating demand plays an important role in the building's total heating demand, the exhaust air heat recovery is inevitable. It is possible to recover only sensible heat or both sensible and latent heat from the exhaust air [3]- [5]. Energy is used to cover the heat losses due to ventilation air and to move the ventilation air for mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%